Effect of Neo-Adjuvant Chemotherapy On Estrogen Receptor (ER), Progesterone (PR) Receptor, Human Epidermal Growth Factor Receptor 2 (HER2), And Ki-67 Index in Breast Carcinoma - Khan, Wajahat Ahmed; Asif, Muhammad; Din, Hafeez Ud; Zafar, Nadeem; Rashid, Farhat; Tariq, Hassan; Aslam, Umair (Pakistan Armed Forces Medical Journal, 2026)
Objective: To know the outcome of neo-adjuvant therapy on hormone receptors, HER2, and Ki-67 index in invasive breast carcinoma. Study Design: Prospective analytical study Place and Duration: Histopathology department, Armed Forces Institute of Pathology, Rawalpindi, Pakistan, from Dec 21 to Oct 22. Methodology: We included 110 patients with histologically proven invasive breast carcinoma in our study. Rate of expression of ER, PR, HER2, and Ki-67 index was assessed in pre-neoadjuvant needle-core specimens, followed by administration of neo-adjuvant chemotherapy, and then the receptor statuses were evaluated on surgically excised specimens of the same patients. A paired t-test was applied to analyse the changes in receptor expression. Results: Among 110 patients, the average age was 48.47±10.12 years. The most common histological type was invasive ductal carcinoma, no special type noted in 97 (88.2%), and the most common histological grade was II, noted in 66 (60%). Discordance of ER is noted in 34 (30.91%) cases, and for PR in 29 (26.37%) cases. Overall, HER2 receptor negativity increased from 41 (37.30%) to 51 (46.40%) cases. The average Ki-67 index decreased from 27.34% to 24.03% after administration of chemotherapy. Conclusion: Neo-adjuvant chemotherapy administration may cause changes in receptor expression, mainly in ER and Ki-67 index. These findings are helpful in the choice of sequential adjuvant therapy and improve treatment and prognosis in invasive breast carcinoma.